Levels of insulin and HOMA-IR in adolescents in Saltillo, Coahuila, Mexico - González Zavala, M. A.; Velasco Morales, A.; Terrazas Flores, J. J.; Cruz Galicia, María Guadalupe de la; Cepeda Nieto, A. C.; Hernández del Río, A. (UANL. Facultad de Medicina, 2015)
An alarming rise of obesity in adolescents has been observed, placing them at risk of developing resistance to insulin (IR) and its adverse metabolic consequences such as diabetes mellitus type 2 (DM2), metabolic syndrome and cardiovascular disease. Objective: To know the prevalence of obesity, and the levels of glucose, insulin and HOMA-IR and its association with the BMIz, waist circumference and the pubertal stage in a random sample of adolescents. Materials and methods: 292 adolescents between 12 and 15 years (152 female and 140 male), whose anthropometric measurements (weight, height and waist circumference) were taken, body mass index calculated and Z-score determined. Blood glucose and insulin levels were evaluated from a sample of blood and their HOMA-IR was determined. Results: The results showed that 32.5% were obese, 22.3% were overweight and 23.6% showed adolescent central obesity. Glucose levels (p = 0.016), insulin (p = 0.0001) and HOMA-IR (p = 0.0001) showed significant differences in the group with obesity. Values of the three parameters were increased with the stage of puberty. We found significant differences in the levels of glucose (p = 0.0388), insulin (p = 0.0005) and HOMA-IR (p = 0.0001) between the prepubertal and postpubertal stages.